Cocoa Fermentech: Inovasi Fermentasi Kakao Berbasis Iot dengan Real- Time Monitoring untuk Optimalisasi Kualitas dan Pendapatan Kelompok Tani Kakao Taram - Febtriko, Anip; Syafrijon Syafrijon; Syukhri Syukhri (Jurnal Pengabdian Masyarakat, 2025)
The Cocoa Fermentech program is a community service activity focused on innovative cocoa fermentation technologies based on Internet of Things (IoT) technology to improve crop quality and the income of cocoa farmer groups in Nagari Taram, West Sumatra. The main problem faced by partners is the fermentation process, which is still carried out traditionally, without standardized temperature, humidity, and pH controls, resulting in suboptimal cocoa bean quality and low product competitiveness. Through this program, the community service team introduced a fermentation SMART-BOX integrated with IoT sensors and a real-time monitoring application. This technology enables farmers to digitally record and monitor fermentation parameters, enabling more data-driven decision-making. In addition, a series of supporting activities were carried out, including technology and management training, outreach, publications, and visual documentation for dissemination. The program results showed significant improvements in the technical and managerial aspects of the farmer groups. Technically, the quality of cocoa fermentation has become more consistent with improved aroma and flavor. From a management perspective, partners have become accustomed to using digital record-keeping, organizing logistics, and documenting activities in a structured manner. This capacity building not only strengthens the competitiveness of local cocoa products, but also encourages the sustainability of technology-based innovation in agricultural product management at the farmer level.